HUBUNGAN KETERLIBATAN SISWA DALAM MELAKUKAN KEGIATAN AKTIVITAS PEMBELAJARAN PJOK MELALUI METODE DIRECT INSTRUCTION MODEL SISWA KELAS IV SD NEGERI 12 CIMPARUH KOTA PARIAMAN - Iqbal DekoPutra; Mardepi Saputra; Nurul Ihsan; Haripah Lawanis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem in this study is the suboptimal and maximal involvement of students in carrying out PJOK learning activities of fourth-grade students of SD Negeri 12 Cimparuh, Pariaman City. The purpose of this study was to determine the relationship between student involvement and carrying out PJOK learning activities directly, both partially and simultaneously. The research method used in this study was the correlational method. The study population was 16 fourth-grade students of SD Negeri 12 Cimparuh, Pariaman City. The sampling technique used was nonprobability sampling with the type of nonprobability sampling being purposive sampling. The results of the correlation coefficient calculation were then interpreted to determine the level of relationship between the two variables. If the calculated r value is greater than the table r at a significance level of 0.05, it can be concluded that there is no significant relationship between student involvement in learning and PJOK learning activities through the Direct Instruction method in fourth-grade students of SD Negeri 12 Cimparuh, Pariaman City. The results of the correlation analysis research show (1) student involvement and (2) carrying out PJOK learning activities through the direct instruction model method for fourth-grade students at SD Negeri 12 Cimparuh, Pariaman City, then the calculated r is 0.382 < rtable 0.497. This means that there is no relationship between student involvement in carrying out PJOK learning activities through the direct instruction model method for fourth-grade students at SD Negeri 12 Cimparuh, Pariaman City.